The Permafrost Young Researchers Network (PYRN) is getting older: The past, present, and future of our evolving community. (7th February 2019) - Tanski, George; Bergstedt, Helena; Bevington, Alexandre; Bonnaventure, Philip; Bouchard, Frédéric; Coch, Caroline; Dumais, Simon; Evgrafova, Alevtina; Frauenfeld, Oliver W.; Frederick, Jennifer; Fritz, Michael; Frolov, Denis; et al.
Abstract: A lasting legacy of the International Polar Year (IPY) 2007–2008 was the promotion of the Permafrost Young Researchers Network (PYRN), initially an IPY outreach and education activity by the International Permafrost Association (IPA). With the momentum of IPY, PYRN developed into a thriving network that still connects young permafrost scientists, engineers, and researchers from other disciplines. This research note summarises (1) PYRN's development since 2005 and the IPY's role, (2) the first 2015 PYRN census and survey results, and (3) PYRN's future plans to improve international and interdisciplinary exchange between young researchers. The review concludes that PYRN is an established network within the polar research community that has continually developed since 2005. PYRN's successful activities were largely fostered by IPY. With >200 of the 1200 registered members active and engaged, PYRN is capitalising on the availability of social media tools and rising to meet environmental challenges while maintaining its role as a successful network honouring the legacy of IPY.